A Study on Reverse Mortgage of SBI - Sravanthi, N. (Indian Journal of Finance, 2010)
The concept of Reverse Mortgage (RM) is gaining momentum in India with the Finance Minister P. Chidambaram giving his nod in the Union Budget for 2007-08. Subsequently, the National Housing Bank (NHB), a subsidiary of the Reserve Bank of India (RBI), released the guidelines. This had led several banks to announce their intentions to launch the scheme. Taking the lead, Dewan Housing Finance Limited (DFHL) followed by Punjab National Bank (PNB) and Bank of Baroda (BOB), States Bank of India (SBI), etc. announced the scheme aimed at senior citizens.In a regular mortgage, a borrower mortgages his new/existing house with the lender in return for the loan amount, the same is charged at a particular interest rate and runs over a predetermined tenure. The borrower then has to repay the loan amount in the form of Equated Monthly Installments (EMIs), which comprise of both principal and interest amounts. The property is utilized as a security to cover the risk of default on the borrower’s part.